Moduli difference of successive inverse coefficients for certain classes of close-to-convex functions - Kumar, Virendra (Ricerche di matematica, 2024)
In this paper, we answer the questions raised in the paper [On the difference of inverse coefficients of univalent functions, Symmetry, 2020, 12(12), art. 2040, 14pp] by Sim and Thomas, and aim to verify the conjecture posed therein in certain cases. For this purpose, we investigate sharp bounds on moduli difference of successive inverse coefficients for certain classes of close-to-convex functions.